2003
DOI: 10.1080/1042819031000068025
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Level of Tumor Necrosis Factor-alpha (TNF-α) Correlates with Leukocytosis and Biological Features of Leukemic Cells, but not Treatment Response of Children with Acute Lymphoblastic Leukemia

Abstract: We have analyzed the clinical significance of the plasma level of tumor necrosis-alpha (TNF-alpha) detection in childhood acute lymphoblastic leukemia (ALL) at diagnosis. 49 patients (pts) with B-lineage ALL (3-17 years of age) and 30 healthy children (age-related control) were enrolled in study. The mean value of the level of TNF-alpha was 43.4 +/- 8.1 pg/ml in ALL pts and 30.7 +/- 3 pg/ml in control. In ALL pts the level of TNF-alpha positively correlated with blast cell count in peripheral blood (R = +0.432… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 3 publications
1
10
0
1
Order By: Relevance
“…TNFα is highly expressed in different leukemia subtypes (Tsai et al, 2011;Volk et al, 2014). The plasma level of TNFα has been associated with leukocytosis in ALL, whereas in CML, TNFα enhances proliferation and survival of the malignant cells (Gallipoli et al, 2013;Potapnev et al, 2003). Placental growth factor (PlGF) is secreted by certain stromal cells in CML and was found to increase angiogenesis in the bone marrow and to promote CML proliferation and aggressiveness of the disease (Schmidt et al, 2011).…”
Section: Role Of the Bmm In Chemoresistancementioning
confidence: 99%
“…TNFα is highly expressed in different leukemia subtypes (Tsai et al, 2011;Volk et al, 2014). The plasma level of TNFα has been associated with leukocytosis in ALL, whereas in CML, TNFα enhances proliferation and survival of the malignant cells (Gallipoli et al, 2013;Potapnev et al, 2003). Placental growth factor (PlGF) is secreted by certain stromal cells in CML and was found to increase angiogenesis in the bone marrow and to promote CML proliferation and aggressiveness of the disease (Schmidt et al, 2011).…”
Section: Role Of the Bmm In Chemoresistancementioning
confidence: 99%
“…In comparison to patients with plasma levels of TNF-α below the median value, they revealed that patients with plasma levels of TNF-α above the median value had considerably greater white blood cell and blast counts in peripheral blood. As a result, their findings show that an elevated TNF-α plasma level is a useful marker for assessing disease activity/progression, but not for predicting the prognosis of childhood ALL [ 16 ]. Drabko et al discovered that serum TNF-α levels were higher in children with ALL compared to the control group [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNF promotes the progression of several hematopoietic tumors by participating in several signaling pathways, including NF-κB, and PI3K/Akt [44,45]. It has been reported that TNF can be produced by various leukemia cells, including AML [36], ALL [46], CML [47], CLL [48], and so on. There was also evidence showing that TNF induced MMP9 expression or secretion in leukemia cells [49].…”
Section: Weighted Compound-target Bipartite Networkmentioning
confidence: 99%